GAMBARAN SELF REGULATED LEARNING PADA MAHASISWA PROGRAM STUDI PSIKOLOGI UNIVERSITAS “X” - Devi Jatmika; Shanty Sudarji; Dina Argitha (Universitas Bunda Mulia, 2013)
Students can be motivated by many ways dan the most ultimate issue is to understand how and why students are motivated for academic achievement. Self regulated learning (SRL) is defined as a concept about how a leaner becomes the master of his own learning process. The aim of this research is to obtain the decription of self regulated learning of Psychology students of “X” University. SRL in this research was measured by using a questionnaire named Motivated Strategies for Learning Questionnaire (MSLQ). MSLQ is constructed by Self regulated learning by Pintrich, Smith, Garcia dan McKeachie (1991). The research method in this research is descriptive quantitative research. Total subjects in this research were 71 Psychology students who engaged studying in 2012/2013 term. The realibility of this research was 0.953. Data analyzed by Z-score and the result revealed that 34 subjects (47.88%) had low SRL, 26 subjects (36.61%) had moderate SRL, and 11 subjects (15.49%) had high SRL. Thus, this research concluded the description of SRL of Psychology students of “X” University was in low category. Keywords: Self Regulated Learning (SRL), Motivation, Learning Strategy